2020
DOI: 10.7759/cureus.7539
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Two Different Thyroid Malignancies: A Collision Phenomenon

Abstract: The term "collision tumor" is described as the coexistence of two or more histologically distinct neoplastic morphologies separated by normal tissue in the same organ. Simultaneous papillary thyroid carcinoma (PTC) and follicular thyroid carcinoma (FTC) of the same thyroid lobe is a very rare pathology. Herein, we report a case of PTC and FTC of the same thyroid lobe. A 79year-old man was evaluated at our hospital for the presence of left hip pain of two-month duration after sustaining a physical trauma to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 11 publications
1
28
0
Order By: Relevance
“…Collision tumors of PTC and follicular thyroid carcinoma (FTC) are thought to be rare and therefore there is a paucity of clinical data on this topic [5,16]. However, Won Gu Kim et al found that the occurrence rate of PTC in patients with follicular thyroid carcinoma was 19% (50 of the 268 FTC patients) and that most of PTC components were microcarcinomas [17].…”
Section: Variants Of Thyroid Collision Tumorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Collision tumors of PTC and follicular thyroid carcinoma (FTC) are thought to be rare and therefore there is a paucity of clinical data on this topic [5,16]. However, Won Gu Kim et al found that the occurrence rate of PTC in patients with follicular thyroid carcinoma was 19% (50 of the 268 FTC patients) and that most of PTC components were microcarcinomas [17].…”
Section: Variants Of Thyroid Collision Tumorsmentioning
confidence: 99%
“…FTC is the second most common type of thyroid carcinoma and tends to disseminate hematogenous leading to lung, bone and central nervous system metastases [5,16]. Hematogenous and distant metastatic invasion is less common in PTC, and intrathyroidal and cervical multicentric disease is more frequent, pleading for lymphatic spread [5,18].…”
Section: Variants Of Thyroid Collision Tumorsmentioning
confidence: 99%
See 3 more Smart Citations